2015
DOI: 10.1039/c5cs00600g
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferases: mechanisms and applications in natural product development

Abstract: Glycosylation reactions mainly catalyzed by glycosyltransferases (Gts) occur almost everywhere in the biosphere, and always play crucial roles in vital processes. In order to understand the full potential of Gts, the chemical and structural glycosylation mechanisms are systematically summarized in this review, including some new outlooks in inverting/retaining mechanisms and the overview of GT-C superfamily proteins as a novel Gt fold. Some special features of glycosylation and the evolutionary studies on Gts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
220
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(237 citation statements)
references
References 293 publications
(326 reference statements)
5
220
0
4
Order By: Relevance
“…7). Similar mutations in plant and human UGTs have shown equivalent results (29). These results suggest that UGT58A1 utilizes a classic catalytic mechanism in which His47 acts as a general base and catalytic residue for enzymatic activity to abstract a proton from the acceptor substrate.…”
Section: Figsupporting
confidence: 50%
See 2 more Smart Citations
“…7). Similar mutations in plant and human UGTs have shown equivalent results (29). These results suggest that UGT58A1 utilizes a classic catalytic mechanism in which His47 acts as a general base and catalytic residue for enzymatic activity to abstract a proton from the acceptor substrate.…”
Section: Figsupporting
confidence: 50%
“…UGT58A1 showed the highest identity (20%) to the template UGT85H2 in the Protein Data Bank, a (iso)flavonoid UGT from Medicago truncatula. Structure-based research on UGT85H2 revealed that an acceptor-His21-Asp125 triad was formed to accomplish the glycosylation reaction, which is similar to the serine hydrolases (28,29). In the serine hydrolase, the histidine group of the catalytic triad of Ser-His-Asp deprotonates serine for nucleophilic attack at the substrate; protonation of the histidine is subsequently stabilized through an interaction with the aspartate (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the identified GT-C enzymes are integral membrane proteins with non-Leloir, inverting GT activity and many are involved in N-glycosylation of proteins (Liang et al 2015). They typically require a divalent cation for activity and use a lipid-phosphate as the sugar donor.…”
Section: Glycosyltransferase Tertiary Structurementioning
confidence: 99%
“…Glycosyltransferases represent a very large family of enzymes that determine the biosynthesis of glycans by group-transfer reaction. In this reaction, the monosaccharide moiety of a simple nucleotide sugar donor substrate, such as UDP-Gal (Uridine diphosphate galactose), GDP-Fuc (Guanosine 5’-diphospho-fucose), or CMP-Sia (Cytidine 5’-monophospho-N-acetylneuraminic acid), is transferred to the acceptor substrate that includes oligosaccharides, monosaccharides, polypeptides, lipids, small organic molecules, and even DNA [59]. These enzymes, not only act in intracellular medium, but they also contribute to the glycosylation of cell surface receptors and extracellular matrix components, modulating signaling pathways and tumor behavior [60, 61].…”
Section: Hypoxia Regulates Glycosyltransferases Glycosidases and Nucmentioning
confidence: 99%